Ханафитский мазхаб и его трактовка вакфа - Конкин, Д.В. (Материалы по археологии, истории и этнографии Таврии, 2005)
Главными источниками, участвовавшими в формировании мусульманского лрава, и которые принимаются всеми суннитскими мазхабами, служат Коран, сунна и иджма. Однако, если Коран принимался безоговорочно, то в отношении сунны и иджма мусульманскими правовыми школами порой предъявлялись некоторые условия для их использования в праве. Hanifa’s Mazhab is a branch of Sunni school of law. The given publication analyses typical features to distinguish Mazhab Uom the other directions of Moslem law. Vakuf{waqt) is characterized as an interesting and original piece of Oriental law. Vakuf is inalienable property withdrawn from civil circulation and devoted to God to serve for a special purpose, usually a noble one. Although the given concept existed in all Mazhabs, every Mazhab interpreted it in a different way. The article analyses va/fuf following the interpretation of Hanifa’s school